(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Following the redistribution of world powers and the end of a unipolar phase, modern tools have emerged to demonstrate the presence of international powers in the global conflict arena. States have prioritized their relations with each other according to these instruments. The most prominent of which was energy and biofuels, where the Cold War erupts between the international powers and its natural gas pillar. In this research, the author tends to shed light on the reality of this energy in the most important global poles, and to show its economic impact in drawing and determining the state relations related to its counterparts around the world. The research deals with the study of both US and Russian gas production, and the relationship between the affected parties that have link with the largest consumer market in Europe. In addition to the Middle East gas, which was discovered in huge quantities and qualitative characteristics that reflected the prestigious international status of the region in the future, and explained the attention since then. في أعقاب إعادة توزع القوى العالمي، وانتهاء مرحلة أحادية القطبية، برزت أدوات حديثة لإثبات وجود القوى الدولية في ساحة الصراع العالمي. وأعيد ترتيب الأولويات لدى الدول في علاقاتها مع بعضها البعض تبعاً لهذه الأدوات. والتي كان أبرزها الطاقة والوقود الحيوي حيث الحرب الباردة التي تندلع بين القوى الدولية وعمادها الغاز الطبيعي وفي البحث أدناه، ينحى الباحث لأن يسلط الضوء على واقع هذه الطاقة لدى أهم الأقطاب العالمية، وإظهار أثرها الاقتصادي في رسم وتحديد علاقات الدولة ذات الصلة بنظيراتها حول العالم. حيث يعنى البحث بدراسة كل من الإنتاج الغازي الأمريكي والروسي، وعلاقة المؤثر والمتأثر التي تربطه باقتصاديات أوروبا كأكبر سوق مستهلكة. بالإضافة لغاز الشرق الأوسط والذي اكتشف بكميات هائلة، وخصائص نوعية عكست المكانة الدولية المرموقة للمنطقة مستقبلاً، وفسرت توجه الأنظار نحوها منذ الوقت الحالي.